EFEKTIVITAS DAN KENYAMANAN TRANCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) DALAM MENGURANGI NYERI KRONIK MUSKULOSKELETAL PADA USIA LANJUT - FITRIYANI, FITRIYANI (2010)
As general, processing aging start at 45 years old and will get a problem at 60 years old or above. Changing of function structure, either physical and mentality will influence ability to someone toward his function, elderly with aging process had an effect to disease appearance, curative and needed recovery. Changing on body system, one of them is musculoskeletal system, system musculoskeletal is a network from muscle, joint and slack. Function of physiotherapy at case musculoskeletal in decrease pain can apply on therapies, namely with TENS. Objective is aim to know differences between Conventional TENS with AL TENS in effectiveness and comfortable to decrease musculoskeletal chronic pain at elderly in house of elderly Wredha Dharma Bhakti of Surakarta. Research method: this research is experiment research with Pre test - post test approach. Technique Sampling is purposive sampling method with total sample are 20 responders. Result of research : Conversional TENS is more effective than AL TENS in decrease musculoskeletal chronic pain, Conversional more comfort than AL TENS in decrease musculoskeletal chronic pain at elderly in house of elderly Wredha Dharma Bhakti of Surakarta.